LINGUO-STYLISTIC CHARACTERISTICS OF THE “GUOFENG” POEMS IN THE “SHIJING” CANON AND SPECIFICS OF THEIR TRANSLATION INTO UKRAINIAN - PIKHTOVNIKOVA, Lidiia; MOSKALENKO, Maryna (Accents and Paradoxes of Modern Philology, 2025)
The article explores issues raised by scholars when studying the Shijing canon, particularly the Guofeng section. The genre, composition, stylistics, and rhythmic-melodic aspects are examined, as well as the problem of rhyme loss due to changes in word pronunciation over centuries since the creation of the Shijing. The article explains the concept of “liu yi” studied by Chinese researchers, and the genre-stylistic categories: fu, bi, and xing, which are important terms for linguo-stylistic analysis of the poems. The translation features highlighted include the presence of culture-specific words and lacunae with no direct equivalents in the target language, the polysemy of hieroglyphs and their ability to transition between parts of speech, a complex system of service word meanings that changed over time, and the need to preserve the laconism and artistic features of the original text. The success of translating the Shijing poems depends on the translator's skills, cultural awareness, ability to balance different translation strategies, preserve the communicative function of the original text, and understand the sociocultural context of ancient Chinese poetry. Five texts in the translation conducted by the author (Moskalenko M.) are compared with existing English translations, considering compositional and stylistic characteristics such as parallelism, rhetorical questions, anaphora, epiphora, and rhythmicity, despite occasional rhyme absence. The poems are usually divided into three parts, though full repetitions make precise demarcation challenging. Stanzas are symmetrically organized, with line and hieroglyph numbers varying. Traditional concepts of fu (direct narration), bi (comparison), and xing (allegorical introduction) intertwine in a complex system of artistic techniques forming the stylistics of the examined poems. Techniques like onomatopoeia, homophones, and hyperbole are used. The research resulted in developing translation rules for ancient Chinese poetry, applied to the author's translation.